PENERAPAN KONSEP ZERO RUNOFF DALAM MENGURANGI VOLUME LIMPASAN PERMUKAAN (PERUMAHAN PURI BALI, DEPOK) - Endah Lestari (FORUM MEKANIKA, 2016)
The population growth rate coupled with increased urbanization process cause increase in fulfillment ofthe Housing and Building Social supported. Due to water runoff the accretion of these buildings led toincrease in the water many translucent layers not caused and reduced the amount of open land/green space.This causes the rain water not translucent / radio infiltrated into the ground but directly runoff into drainagechannels, river or sea. Under these circumstances it is necessary to develop methods of managing rain water,rain harvesting and rain water utilizing. To cope with rain runoff that caused by rain water. One way is toapply the concept of Zero Runoff technology in general and the residential area facilities. Zero Runoff is amust to each of the building may not cause an increase of rain water discharge into a drainage channelsystem or river systems flow. Some of the concepts concept technology of Zero Runoff are Rain Water Tank,Rain and Infiltration Wells, Rain water Infiltration Pond.